AB0928 Ustekinumab and tnf inhibitors in psoriatic arthritis: first follow-up data from a routine care study in 8 european countries (PSABIO). (12th June 2018) - Smolen, J.S.; Bergmans, P.; Bondareva, I.; de Vlam, K.; Gremese, E.; Joven-Ibáñez, B.; Korotaeva, T.V.; Nurmohamed, M.T.; Sfikakis, P.P.; Siebert, S.; Smirnov, P.; Theander, E.; et al.
Abstract : Background: The purpose of PsABio (ClinicalTrials.gov Id: NCT02627768 ) is to evaluate the efficacy, tolerability and persistence of TNF inhibitors (TNFi) and ustekinumab (UST) for patients with psoriatic arthritis (PsA) starting 1st, 2nd or 3rd line biologic disease-modifying antirheumatic drugs (bDMARDs) in real-world routine care. Objectives: Here we present the first interim follow-up data on joint-related outcomes. Methods: Of 278 UST- and 285 TNFi-treated patients consecutively enrolled between Dec 2015 and, Aug 2017 152 and 151, respectively, had data available at 6 months for their initial line of treatment. Joint-related outcomes, as observed data, were compared between baseline and 6 months within the treatment cohorts. Results: Among all enrolled patients, 7.6% of UST- and 10.2% of TNFi-treated patients stopped or switched to another bDMARD before the 6 month timepoint. For those with 6 month data for their initial bDMARD, UST was used as the first-line bDMARD in 40.1%, as 2nd in 35.5%, and as 3rd in 24.3% of patients; these numbers were 64.2%, 28.5%, and 7.3%, respectively, for TNFi. DAS28 scores improved significantly at 6 months from mean baseline values of 4.3 (SD 1.2) and 4.3 (SD 1.2) for UST and TNFi, respectively, by means of −1.3 (95% CI: −1.6, −1.0) and −1.3 (95% CI: −1.6, −1.1). Significant improvements were seen in both cohorts across all treatment lines (table 1) and subtypes of PsA (data not shown). Minimal disease activity (MDA) was achieved at 6 months for 28.8% of UST- and 29.7% of TNFi-treated patients. CDAI results similarly and significantly improved. For the DAPSA, equally, statistically significant improvements were seen: mean −18.4 (95% CI: −22.2, −14.5) and −19.5 (95% CI: −22.5, −16.5) for UST and TNFi, respectively, with 12.2% and 15.7% reaching DAPSA remission and 37.8% and 37.1% reaching low disease activity. cDAPSA showed similar improvement. For details on components of the DAS28 and of the DAPSA, see table 1. Axial joint involvement was significantly improved with reductions in BASDAI and ASDAS. Conclusions: Both UST- and TNFi-treated patients showed statistically significant and considerable improvements in joint-related measures after 6 months in a real-world setting, irrespective of whether first or further line of treatment. Acknowledgements: This study was sponsored by Janssen. Disclosure of Interest: J. Smolen Grant/research support from: Received grants for his institution from AbbVie, Janssen, Lilly, MSD, Pfizer, and Roche, Speakers bureau: Provided expert advice to and/or had speaking engagements with AbbVie, Amgen, Astra-Zeneca, Astro, Celgene, Celtrion, GlaxoSmithKline, ILTOO, Janssen, Lilly, Medimmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung, Sanofi, and UCB, P. Bergmans Shareholder of: Johnson and Johnson, Employee of: Janssen, I. Bondareva Grant/research support from: Served as investigator for clinical trials sponsored by Pfizer, Janssen, Biocad, K. de Vlam Consultant for: Johnson and Johnson, E. Gremese Consultant for: AbbVie, Janssen, Lilly, Pfizer, Speakers bureau: AbbVie, Janssen, Lilly, Pfizer, B. Joven-Ibáñez Speakers bureau: Celgene, Novartis, MSD, Pfizer, AbbVie, and Janssen, T. Korotaeva Consultant for: Pfizer, MSD, Novartis, AbbVie, Celgene, Biocad, Janssen, and UCB, Speakers bureau: Pfizer, MSD, Novartis, AbbVie, Celgene, Biocad, Janssen, and UCB, M. Nurmohamed Grant/research support from: Received research support to his institution from Pfizer, AbbVie, Roche, BMS, MSD, Mundipharma, UCB, Janssen, Menarini, Eli Lilly, Sanofi, and Celgene, Consultant for: Pfizer, AbbVie, Roche, BMS, MSD, Mundipharma, UCB, Janssen, Menarini, Eli Lilly, Sanofi, and Celgene, Speakers bureau: Pfizer, AbbVie, Roche, BMS, MSD, Mundipharma, UCB, Janssen, Menarini, Eli Lilly, Sanofi, and Celgene, P. Sfikakis: None declared, S. Siebert Grant/research support from: Receipt of grants/research support to his institution from Pfizer, Janssen, BMS, Celgene, UCB, and Boehringer Ingelheim. participation in clinical trials with AbbVie, Novartis, and UCB, Consultant for: AbbVie, UCB, Pfizer, Janssen, Boehringer Ingelheim, Celgene, and Novartis, Speakers bureau: AbbVie, UCB, Pfizer, Janssen, Boehringer Ingelheim, Celgene, and Novartis, P. Smirnov Employee of: Janssen, E. Theander Employee of: Janssen, V. D'Abrosca: None declared, L. Gossec Grant/research support from: Received grants for her institution from Pfizer, Consultant for: Received honoraria from AbbVie, Celgene, Janssen, Lilly, Novartis-Sandoz, Pfizer, Sanofi, and UCB